2022
DOI: 10.3892/ijmm.2022.5089
|View full text |Cite
|
Sign up to set email alerts
|

XBP1s promotes the development of lung adenocarcinoma via the p‑JNK MAPK pathway

Abstract: Spliced X-box binding protein 1 (XBP1s) has been reported to participate in the pathogenesis of numerous types of cancer; however, whether XBP1s plays a role in lung cancer remains to be elucidated. In the present study, bioinformatics analysis was performed to determine the mRNA expression level of XBP1 in lung cancer and adjacent normal tissues. Gene Ontology terms, pathway enrichment and Pearson's correlation analysis were performed to investigate the possible mechanism involved. Western blot and reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As shown in Figure 2b, FR‐EPs exhibit two thermal oxidative degradation processes, showing the similar decomposition behaviors with EP. The addition of phosphorus‐containing FRs usually causes the decrease of thermal stability 38,39 . However, the incorporation of AlPi and nickel alginate do not change the T 5% , T max1 , R max1 , T max2 , and R max2 of EP, which can be attributed to the lower content (4%) of AlPi and nickel alginate.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure 2b, FR‐EPs exhibit two thermal oxidative degradation processes, showing the similar decomposition behaviors with EP. The addition of phosphorus‐containing FRs usually causes the decrease of thermal stability 38,39 . However, the incorporation of AlPi and nickel alginate do not change the T 5% , T max1 , R max1 , T max2 , and R max2 of EP, which can be attributed to the lower content (4%) of AlPi and nickel alginate.…”
Section: Resultsmentioning
confidence: 96%
“…The addition of phosphorus-containing FRs usually causes the decrease of thermal stability. 38,39 However, the incorporation of AlPi and nickel alginate do not change the T 5% , T max1 , R max1 , T max2 , and R max2 of EP, which can be attributed to the lower content (4%) of AlPi and nickel alginate. And the char residues at 700 C of FR-EPs are achieved to 2.5% (EP/AlPi), 2.9% (EP/AlPi 9.5 -Nickel Alginate 0.5 ) and 2.7% (EP/AlPi 9.0 -Nickel Alginate 1.0 ), which are obviously higher than that of EP (0.4%).…”
Section: Thermal-oxidative Stability In Air Atmospherementioning
confidence: 90%
“…Numerous studies have shown that the JNK/MAPK pathway significantly affects the development of cancer cells in various tumours. Specific p‐JNK inhibition can considerably reduce the proliferation and migration of cancer cells such as lung adenocarcinoma, oesophageal squamous cell carcinoma, and colon cancer cells, and can greatly induce the apoptosis of some cancer cells 38–41 . By influencing the expression of many molecules, the JNK signalling pathway can increase the growth and metastasis of cancer cells, whereas JNK activation can also inhibit apoptosis by inducing autophagy in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]33 can greatly induce the apoptosis of some cancer cells. [38][39][40][41] By influencing the expression of many molecules, the JNK signalling pathway can increase the growth and metastasis of cancer cells, whereas JNK activation can also inhibit apoptosis by inducing autophagy in various cancers. In cancer treatment, the activation of JNK pathway can promote the expression of PD-L1, thereby enhancing the immune escape of tumours.…”
Section: Discussionmentioning
confidence: 99%